2010
DOI: 10.1146/annurev.clinpsy.121208.131305
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Depression: Current Status and Future Directions

Abstract: Cognitive theories of depression posit that people's thoughts, inferences, attitudes, and interpretations, and the way in which they attend to and recall information, can increase their risk for depression. Three mechanisms have been implicated in the relation between biased cognitive processing and the dysregulation of emotion in depression: inhibitory processes and deficits in working memory, ruminative responses to negative mood states and negative life events, and the inability to use positive and rewardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

84
1,534
8
24

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,934 publications
(1,650 citation statements)
references
References 164 publications
84
1,534
8
24
Order By: Relevance
“…De Raedt & Gotlib & Joormann, 2010). Although there is extensive evidence supporting attention, interpretation, and memory biases in depression, the interplay between these cognitive mechanisms is not well understood.…”
Section: Indirect Effect Of Attention On Memory 3 Indirect Effects Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…De Raedt & Gotlib & Joormann, 2010). Although there is extensive evidence supporting attention, interpretation, and memory biases in depression, the interplay between these cognitive mechanisms is not well understood.…”
Section: Indirect Effect Of Attention On Memory 3 Indirect Effects Ofmentioning
confidence: 99%
“…Various cognitive variables at the content (e.g., dysfunctional attitudes) as well as at the process (e.g., memory) level that play a detrimental role in the onset and maintenance of depressive symptoms have been identified. At the process level, considerable empirical research has shown that both subclinically and clinically depressed individuals selectively attend to negative information, tend to interpret ambiguous information in a negative manner, and recall disproportionately more negative memories (for reviews, see Gotlib & Joormann, 2010). Although there is extensive evidence supporting attention, interpretation, and memory biases in depression, the interplay between these cognitive mechanisms is not well understood.…”
mentioning
confidence: 99%
“…Several researchers have already associated depression with deficits in cognitive control (Hertel, 1997;Gotlib & Joormann, 2010). Moreover, it has been stated that these deficits are not only present during depression, but that impairments in cognitive control after remission would be predictive of future depression (Joormann & D'Avanzato, 2010).…”
Section: Rumination Mediates the Relationship Between Impaired Cognitmentioning
confidence: 99%
“…Las personas con depresión tienen dificultades para desengancharse de material negativo una vez que éste captura su atención (Gotlib y Joormann, 2010;Sánchez, Vázquez, Marker, Lemoult y Joormann, 2013). Dicha dificultad de desenganche probablemente está también ligada a una mayor tendencia a quedarse atrapado en pensamientos rumiativos (Nolen-Hoeksema, Wisco y Lyubomirsky, 2008), lo que se considera un estilo de procesamiento indicador de vulnerabilidad a la depresión (Vázquez et al, 2010).…”
Section: Cognición Emoción Y Depresiónunclassified
“…ej. : atencionales) asociados a determinadas estructuras y circuitos cerebrales, pueden estar ligados mediante procesos complejos de feedback a procesos cognitivos más complejos y a consecuencias emocionales y conductuales características de la depresión (De Raedt y Gotlib y Joormann, 2010;Vázquez et al, 2010).…”
Section: Cognición Emoción Y Depresiónunclassified